2022
DOI: 10.3390/nu14142823
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status after Roux-En-Y (Rygb) and One Anastomosis Gastric Bypass (Oagb) at 6-Month Follow-Up: A Comparative Study

Abstract: Introduction: Roux-en-Y gastric bypass (RYGB) and one anastomosis gastric bypass (OAGB) are two effective bariatric surgical procedures with positive outcomes in terms of weight loss, comorbidities remission, and adverse events profiles. OAGB seems to carry a higher risk of malnutrition, but existing data are controversial. The aim of this study is to objectively evaluate and compare malnutrition in patients undergoing RYGB and OAGB. Methods: Retrospective monocentric study of obese patients undergoing RYGB or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(60 reference statements)
1
9
0
Order By: Relevance
“…However, some of the deficiencies may require longer follow-up periods to develop. Consistent with our data, a recent study found no differences between procedures in nutritional status (using the Controlling Nutritional Status [CONUT] nutrition score) or malnutrition at 6 months [28]. After OAGB, vitamin deficiencies [11] and even malnutrition [3,17] have been reported.…”
Section: Discussionsupporting
confidence: 92%
“…However, some of the deficiencies may require longer follow-up periods to develop. Consistent with our data, a recent study found no differences between procedures in nutritional status (using the Controlling Nutritional Status [CONUT] nutrition score) or malnutrition at 6 months [28]. After OAGB, vitamin deficiencies [11] and even malnutrition [3,17] have been reported.…”
Section: Discussionsupporting
confidence: 92%
“…In an opposite fashion, OAGB saw an unprecedented rise. OAGB is easier to fashion and randomized trials have yielded similar efficacy results to RYGB in the medium term [ 22 , 23 ]. While no OAGB was performed in SICOB centers in 2011, it accounted for as many as 15% of BS in 2021.…”
Section: Discussionmentioning
confidence: 99%
“…It was calculated on three parameters, the serum albumin and total cholesterol levels and the total lymphocyte count. CONUT is usually used to evaluate the prognosis of cancer patients, ( 16 , 36 ). Our study revealed that the ratio of infection of CHF patients with high CONUT score is higher, therapeutic outcomes is poorer, financial burden is heavier.…”
Section: Discussionmentioning
confidence: 99%
“…Controlling Nutritional Status (CONUT) is a scoring system that is used to assess the host's nutrition and immune states ( 16 ). CONUT is calculated from the serum albumin concentration, total blood cholesterol level, and total peripheral lymphocyte count.…”
Section: Introductionmentioning
confidence: 99%